GENDER IMPACT, TYPICAL PROFILES OF ACCESS TO CREDIT AND SAVINGS MARKETS: A CASE OF RURAL HOUSEHOLDS IN COTE D'IVOIRE - Melaine, OUOYA Zrakpa (Studies and Scientific Researches. Economics Edition, 2019)
Unlike the other two components of the financial trinity savings and insurance, the demand for credit has been the subject of much work. Using data from the household standards of living survey in Côte d'Ivoire (ENV2015), we use two logit models to identify the determinants of demand for credit and savings in rural Ivorian. Our work shows that the social, economic and demographic characteristics of the household and its head are significant determinants of demand for those services. The study revealed that each of these two services is a significant determinant of the other. Following this first analysis, we have identified the typical profiles of households with the highest and lowest probabilities of access to savings and credit. Finally, the gender approach of this study has shown that unlike the number of men who has no influence on the demand for savings among households without access to credit, the number of women considerably increases the level of access to credit for households with or without access to savings. And that households led by a woman have a better access to credit.